Gambaran Pengetahuan Ibu Nifas Tentang Perawatan Tali Pusat - Ningtias, Meysifa; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
The newborn mortality rate is one of the indicators used to describe the health status of the community. According to the World Health Organization (WHO), in 2015 the infant mortality rate in the world reached 54 per 1000 live births, in developing countries the infant mortality rate was relatively high and very varied, reaching 11-68 per 1000 live births, while in Southeast Asia the IMR reached 39 per 1000 live births, of which 21% are caused by infection (WHO, 2016). The reason is because there is still a lack of knowledge of mothers in caring for newborns, especially for preventing infection of the umbilical cord. This study aims to describe the knowledge of postpartum mothers regarding umbilical cord care in newborns. This type of research is in the form of a literature review with a descriptive method. This literature search is through publications in two databases, namely Pubmed and Google Scholar. The search strategy method for obtaining journals uses the keywords "Umbilical Cord Care" or "Knowledge". Furthermore, from the search results, the researcher found 179 articles using PubMed, and 6,080 using the appropriate Google Scholar based on keywords. After that, a title screening was carried out according to the topic of the literature review, obtained 4,100 articles and obtained 17 articles that met the inclusion criteria and exclusion criteria. The results of the study obtained 17 articles that examined the level of knowledge of mothers about umbilical cord care. The conclusion of this study is that the level of mother's knowledge influences the care of the umbilical cord in order to reduce the incidence of umbilical cord infection. It is hoped that health workers can play an active role in providing education to the public and can improve the quality and quantity of services so that they can detect abnormalities in pregnant women from an early age and increase counseling about umbilical cord care